Is ulna curvature in the StW 573 ('Little Foot') Australopithecus natural or pathological?. Issue 151 (February 2021) - Araiza, Isabella; Meyer, Marc R.; Williams, Scott A.
Highlights: Previous work suggests curvature of the 'Little Foot' ulna represents pathological bowing from a childhood fall. Shape analysis in apes, hominins and modern humans, including clinical humans rejects the traumatic bowing hypothesis. Instead, the 'Little Foot' ulna reflects a natural degree of curvature observed in apes and many early hominins.